METAFORA ALAM DALAM LIRIK LAGU AIMER - Alhafizh, Farhan Effri; Aibonotika, Arza; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to discuss about metaphors withnatural elements in Aimer's songs lyrics. The method that used in this research isdescriptive qualitative method. The data source of this research comes from the songsthat sung by Aimer in her albums entitiled ‘Walpuris’ and ‘After Dark’. The naturemetaphors that founds in Aimer's songs lyrics are three types of conceptual metaphors,namely structural metaphor, orientational metaphor, and ontologikal metaphor. Thereare also several image schemes used in each nature metaphor, first in the word raime‘rumbling’ has an identity image scheme that namely the similarity of thecharacteristic between rumbling and a loud sound, second in the word hoshikuzu nonaka ‘in stardust’ has a unity/multiplicity image scheme that namely the number ofstars that cannot be counted, and third in the word kaze ‘wind’ which has an existenceimage scheme namely the existence of an object namely the wind.Keywords: Metaphor, Nature, Aimer